2014
DOI: 10.1007/s00247-014-3232-5
|View full text |Cite
|
Sign up to set email alerts
|

The challenging ultrasound diagnosis of perforated appendicitis in children: constellations of sonographic findings improve specificity

Abstract: Our study demonstrates that identification of select constellations of findings using abdominal sonography, in addition to focused US examination of the right lower quadrant, can improve sonographic diagnosis of perforated appendicitis in the pediatric population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 29 publications
(29 reference statements)
4
40
0
Order By: Relevance
“…In the current study, 67% of patients were found to have complicated appendicitis on postoperative pathologic evaluation. Presence of an appendicolith has been shown in previous adult and pediatric studies to be independently associated with complicated appendicitis [13][14][15][16]. Despite all of the patients in this study having a clinical history, examination, and imaging study consistent with acute uncomplicated appendicitis, more than two-thirds of the patients undergoing surgery were found to have complicated appendicitis.…”
Section: Discussionmentioning
confidence: 51%
“…In the current study, 67% of patients were found to have complicated appendicitis on postoperative pathologic evaluation. Presence of an appendicolith has been shown in previous adult and pediatric studies to be independently associated with complicated appendicitis [13][14][15][16]. Despite all of the patients in this study having a clinical history, examination, and imaging study consistent with acute uncomplicated appendicitis, more than two-thirds of the patients undergoing surgery were found to have complicated appendicitis.…”
Section: Discussionmentioning
confidence: 51%
“…The presence and constellation of secondary findings such as complex fluid collections, dilated bowel and RLQ echogenic fat may help distinguish perforated appendicitis from uncomplicated appendicitis [35, 36]. …”
Section: Diagnostic Applications Of Ultrasoundmentioning
confidence: 99%
“…In perforated appendicitis, a phlegmon or abscess may be seen, while the appendix may appear decompressed or may not be visualized [35, 36]. …”
Section: Diagnostic Applications Of Ultrasoundmentioning
confidence: 99%
“…Reflective of the steep learning curve associated with performing US for suspected appendicitis [17], US results are less reliable when the appendix is not visualized [23]. Although the pooled sensitivity and specificity of US for pediatric appendicitis in the literature is high at 88% and 94% [15], US sensitivity for differentiating perforated from acute appendicitis is low [48]. The combined sonographic findings of dilated bowel, right lower quadrant echogenic fat, and complex fluid is associated with 100% specificity for pediatricperforated appendicitis.…”
Section: Discussionmentioning
confidence: 99%